105. Evaluation of a Multiplex PCR Panel for the Microbiologic Diagnosis of Pneumonia in Hospitalized Patients: A Retrospective Analysis from an Academic Medical Center. (31st December 2020) - Zacharioudakis, Ioannis; Zervou, Fainareti; Inglima, Kenneth; See, Benjamin; Aguero-Rosenfeld, Maria E
Abstract: Background: Pneumonia is a leading cause of hospitalization and mortality. Due to the low yield of available diagnostic tests, ATS/IDSA pneumonia guidelines recommend a microbiologic work-up only for hospitalized patients with severe pneumonia. Methods: From 5/2019 to 1/2020, we selected adult patients with clinical and radiographic findings highly suggestive of pneumonia. The BioFire® FilmArray® pneumonia panel was performed on sputum specimens that met quality microbiologic criteria and the results were compared to those of sputum cultures and other tests sent per standard of care. A limit of 10 5 copies/mL was used for positivity in semi-quantitative bacterial targets. The empiric antimicrobial regimen was reviewed to quantify the potential for antimicrobial optimization. Results: Seventy patients were included in the analysis. Median age was 70 (IQR 53.5–81.75), and the majority (43 patients, 61.4%) were classified as Class IV and V using the pneumonia severity index, indicating severe cases of pneumonia. Sixty-nine patients completed at least a 5-day course for pneumonia and 14.3% died during their hospitalization. The fifteen patients (21.4%) that submitted a sputum culture before the initiation of antimicrobial therapy, had a trend towards a positive sputum culture (60% (9/15) vs 36.4% (20/55)) (p=0.09). The BioFire® FilmArray® pneumonia Panel increased the number of patients who received a microbiologic diagnosis from 29 (41%) to 59 (84.3%) (p< 0.001). The per isolate analysis revealed significantly more targets detected for Haemophilus influenzae (p=0.002) and Streptococcus pneumoniae (p=0.05). On review of empiric antimicrobial treatment, there was possibility for antimicrobial optimization in 80% of patients, including 9 cases of pathogens (4 MRSA, 3 Legionella pneumophila, 2 CTX-M gram-negative rods) where the pathogens were not covered and another 70 antimicrobials in 49 patients that could be stopped. Flow chart Bacterial Pathogens Detected in Standard of Care Alone Testing and with the Addition of Pneumonia Panel. Potential for Antimicrobial Optimization Using the Pneumonia Panel Conclusion: Incorporation of the pneumonia panel in the diagnostic work-up of patients hospitalized with pneumonia substantially increased the rate of microbiologic diagnosis and had the potential to guide appropriate antimicrobial therapy. Future studies to quantify the effects on clinical outcomes and cost-effectiveness from tailored therapy are needed. Disclosures: All Authors : No reported disclosures